Natural Products Modulating Angiotensin Converting Enzyme 2 (ACE2) as Potential COVID-19 Therapies - Abubakar, Murtala Bello; Usman, Dawoud; El-Saber Batiha, Gaber; Cruz-Martins, Natália; Malami, Ibrahim; Ibrahim, Kasimu Ghandi; Abubakar, Bilyaminu; Bello, Muhammad Bashir; Muhammad, Aliyu; Gan, Siew Hua; Dabai, Aliyu Ibrahim; Alblihed, M; et al. (Frontiers in Pharmacology, 2021)
The 2019 coronavirus disease (COVID-19) is a potentially fatal multisystemic infection caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Currently, viable therapeutic options that are safe and readily available are desired, but lacking. Nevertheless, the pandemic is noticeably of lesser burden in African and Asian regions, where the use of traditional herbs predominates, with such relationship warranting a closer look at ethnomedicine. From a molecular viewpoint, the interaction of SARS-CoV-2 with angiotensin converting enzyme 2 (ACE2) is the crucial first phase of COVID-19 pathogenesis. Here, we review plants with medicinal properties which may be implicated in mitigation of viral invasion either via direct or indirect modulation of ACE2 activity to ameliorate COVID-19. Selected ethnomedicinal plants containing bioactive compounds which may prevent and mitigate the fusion and entry of the SARS-CoV-2 by modulating ACE2-associated up and downstream events are highlighted. Through clinical trials, these plants could be supported for ethnobotanical use and the phytomedicinal ligands could be potentially developed into preventive therapeutics for COVID-19. This will benefit researchers actively looking for solutions from plant bioresources and help lessen the burden of COVID-19 across the globe.